AN EGALITARIAN OPTIC: SELF-PORTRAITS, SELF-CONSTRUCTION, AND A HOMOSOCIAL ENCOUNTER IN A BANANA PLANTATION - Coleman, Kevin (2015)
In an unpublished image from the 1930s, studio photographer Rafael Platero Paz embraces a white North American man near a river in El Progreso, Honduras. Both men are stark naked and cover only their genitals with leaves. They look directly into the camera. This essay examines Platero Paz’s self-portraits, found in a visual archive made up mostly of photos of peasants and banana laborers, new mothers and local merchants. Invoking Jean-Paul Sartre’s phenomenology of sight, I argue that in his traditional self-portraits, Platero Paz posed for an eventual Other. He was there, waiting for the Other’s recognition and approval. And insofar as the Other was posited as the destination and ideal viewer of these portraits, Platero Paz was declaring: “I am the Other.” In contrast, in the Garden of Eden photo, Platero Paz incorporates the Other into his landscape and declares “I am we,” establishing a homosocial, if not homoerotic, subject-subject relation in the hypermasculine space of a banana plantation.